Optimal Cutoff Points of Anthropometric Parameters to Identify High Coronary Heart Disease Risk in Korean Adults - Kim, Sang Hyuck; Choi, Hyunrim; Won, Chang Won; Kim, Byung-Sung (Journal of Korean medical science, 2016)
Several published studies have reported the need to change the cutoff points of anthropometric indices for obesity. We therefore conducted a cross-sectional study to estimate anthropometric cutoff points predicting high coronary heart disease (CHD) risk in Korean adults. We analyzed the Korean National Health and Nutrition Examination Survey data from 2007 to 2010. A total of 21,399 subjects aged 20 to 79 yr were included in this study (9,204 men and 12,195 women). We calculated the 10-yr Framingham coronary heart disease risk score for all individuals. We then estimated receiver-operating characteristic (ROC) curves for body mass index (BMI), waist circumference, and waist-to-height ratio to predict a 10-yr CHD risk of 20% or more. For sensitivity analysis, we conducted the same analysis for a 10-yr CHD risk of 10% or more. For a CHD risk of 20% or more, the area under the curve of waist-to-height ratio was the highest, followed by waist circumference and BMI. The optimal cutoff points in men and women were 22.7 kg/m(2) and 23.3 kg/m(2) for BMI, 83.2 cm and 79.7 cm for waist circumference, and 0.50 and 0.52 for waist-to-height ratio, respectively. In sensitivity analysis, the results were the same as those reported above except for BMI in women. Our results support the re-classification of anthropometric indices and suggest the clinical use of waist-to-height ratio as a marker for obesity in Korean adults.